„Przypomnij sobie…” (Ap 2,5; 3,3) Duch Święty żywą pamięcią Kościoła w świetle Apokalipsy Janowej - Podeszwa, Paweł Adam (Verbum Vitae, 2020)
The Holy Spirit reminds the Church about everything that Jesus said and did. Two texts from the Book of Revelation clearly point to this function of the Paraclete, who speaks to the community, at the same time referring to its memory, in the Letter to the Church in Ephesus (2:5) and in the Letter to the Church in Sardis (3:3). Both texts contain an imperative "remember". In their light, we attempt to answer the basic question: What does the Holy Spirit remind the Church about? The analyzed texts, in which the Holy Spirit calls upon the Church community to stimulate memory, clearly indicate that the main issue, first and foremost, is about remembering the foundations of the Christian faith (incarnation, paschal mystery) and the identity of Christians united, through baptism, with the crucified and risen Jesus and born into a new life. The call for remembering is tantamount to the need to eagerly guard the deposit of faith and conversion, that is to accept God’s intention and plan, which is supposed to lead to committing concrete acts of faith. The motivation for such an attitude of Christians is the memory of God's kindness and gifts. The Holy Spirit, called by the Catechism of the Catholic Church "the Church's living memory" (1099), stimulating and activating the memory of the community, mobilizes to a living and fruitful faith, which is expressed in a true Christian testimony of belonging to Jesus, brotherly love and zealous proclamation of Good News.